Conjugate-mixed convection heat transfer in a lid-driven enclosure with thick bottom wall - Öztop, Hakan Fehmi; Sun, Changzheng; Yu, Bo (Pergamon-Elsevier Science Ltd, 2008)
Conjugate heat transfer by mixed convection and conduction in lid-driven enclosures with thick bottom wall has been studied by a numerical method. The enclosure is heated from the bottom wall isothermally. Temperature of the top moving wall, which has constant flow speed, is lower than that of the outside of bottom wall. Vertical walls of the enclosure are adiabatic. Governing parameters are solved for a wide range of Richardson numbers (0.1 <= Ri <= 10), ratio of height of bottom wall to enclosure height (0.1 <= h/H <= 0.5) and thermal conductivity ratio (0.01 <= lambda(f)/lambda(s) <= 10). Obtained results showed that heat transfer decreases with increasing of lambda(f)/lambda(s), ratio, Richardson number and thickness ratio of the wall. Flow strength is affected for only higher values of lambda(f)/lambda(s) ratio. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: lid-driven cavity; mixed convection; conjugate; conduction; heat